(untitled) (Research, Society and Development, 2025)
The short gestation period and high number of puppies per birth favor the accelerated growth of the canine population. This highlights the need for population control of these animals through ovariohysterectomy. However, hormonal contraceptives are still used, which can induce disorders such as mammary neoplasia and metritis. This study analyzed the correlation between the incidence of mammary neoplasia and metritis in female dogs treated at veterinary clinics in Araguaína, Tocantins, between 2019 and 2023, and the use of hormonal contraceptives. We observed a positive correlation between the development of diseases, particularly metritis, and the use of contraceptives, especially when used multiple times. Metritis was observed to occur in younger animals, and neoplasia at older ages. However, many medical records lacked information, compromising the analysis. The data highlights the health problems associated with the use of contraceptives but also demonstrates the need for professionals to perform anamnesis and complete medical records more efficiently.